The Indicator Role of Algae in Assessing the Organic Pollution in the Lena River Delta, the Russian Arctic - Gabyshev, Viktor; Barinova, Sophia; Ivanova, Anna; Gabysheva, Olga; Curtean-Bănăduc, Angela (Frontiers in Environmental Science, 2022)
The Lena River forms a delta, one of the largest in the world. The entire territory of the delta is part of the Ust-Lensky State Natural Reserve. The delta is located beyond the Arctic Circle in a continuous permafrost zone. The delta is crossed by numerous channels and has lakes, streams, hollows, swamps. In the Russian Arctic sector, ambitious plans for the development of the oil industries are being implemented. This study goal was to determine the species composition of algae in the Lena River delta and to use their properties as indicators of organic water pollution as evidence of water ecosystem stress. The results of the study revealed 700 species from 10 phyla. Statistical analysis indicate that hydrological conditions are the main factor, which can be a stressor too regulating the spatial structure of the species composition of algal communities in the Lena River delta. The distribution of groups of indicators of organic pollution, trophic state, and type of nutrition of algal cells along the main water channels suggests that now a possible source of organic pollution may be the effect of mixing river and saline waters during high tide. It is evidenced by an increase in the number of mixotrophic organisms and indicators of increased trophic state. Therefore, the integral bioindication as a method that reveals hidden connections in the ecosystem can be useful for monitoring in the period of the accentuated development of the oil industries in this Arctic region.